Do Sin Firms Commit Accounting Sins? - Hanni Liu; Crystal Xu (STIE Malangkucecwara, 2023)
Social norms deter socially responsible investors from investing in sin firms, i.e., firms that sell unethical products and profit from human vice. Existing literature documents that sin firms are less held by institutional investors and less followed by analysts, and this neglect effect leads to higher expected returns than in other firms. Our study explores the earnings management behavior of sin firms. Our empirical findings suggest that compared to others, sin firms are more likely to report small earrings surprises and small earnings increases, but less likely to report superior earnings. Sin firms’ earnings management behavior is exacerbated by lower non-transient institutional ownership, lower analyst coverage, and greater litigation risks. Additional analyses document that sin firms use both accrual-based management and real activity manipulation to report earnings that just meet earnings thresholds. The overall findings suggest that sin firms’ opportunistic behavior likely increases the information risks and contributes to the documented higher expected returns.